Effect of Aminoguanidine and Copper(II) Ions on the Formation of Advanced Glycosylation End Products - Jakuš, Vladimír; Bauerová, Katarína; Rietbrock, Norbert (Arzneimittelforschung, 2001)
Nonenzymatic glycosylation of proteins is a weighty consequence of hyperglyc-aemia in diabetes. This study examines the possible effect of copper(II) ions on the glycosylation of human serum albumin (HSA) and the resulting formation of advanced glycosylation end products (AGEs). HSA in phosphate-buffered saline was incubated with 100 mmol/l glucose. The effect of addition of copper(II) ions and/or aminoguanidine bicarbonate (CAS 2582-30-1) was investigated. The determination of AGE levels derived from glycosylated/glycoxidated HSA was performed using a specific spectrofluoro-metric assay (excitation 346 nm; emission 418 nm). The results showed that the addition of copper(II) ions to the incubation medium containing glucose increased the formation of AGEs. Further, in the presence of copper(II) ions, a significant blockade of aminoguanidine inhibitory effect on the formation of AGEs was observed.
Keywords: Albumin, human serum; Aminoguanidine; Copper(II) ions; Nonenzymatic glycosylation, end products, glycoxidation